Methanol to gasoline (MTG): Intensification of the process in a two-zone fluidized bed reactor (TZFBR) - Sanz Martínez, Andrés; Lasobras, Javier; Soler, Jaime; Herguido, Jaime; Menéndez, Miguel (Jornada de Jóvenes Investigadores del I3A, 2018)
The feasibility of carrying out the production of gasolines from methanol (MTG process) in a two-zone fluidized bed reactor (TZFBR) has been studied for three different catalysts. The catalysts used have been prepared by agglomeration of zeolite HZSM-5 (SiO2/Al2O3= 30) with boehmite or bentonite, as a binder, and alumina. Two configurations of a fluidized bed reactor have been worked on: conventional (FBR) and two-zone (TZFBR). Both, a screening of catalysts and a study of the effect of temperature (400-500ºC) were carried out in the FBR arrangement. Among catalysts tested, the one containing boehmite was found as the most appropriate and it was subsequently used for the experimental validation of the MTG reaction in TZFBR. The three catalysts tested led to a very similar distribution of products, the yield of light hydrocarbons always being higher than that of gasoline. Increasing temperature resulted in an increase in the yield to light hydrocarbons (decreasing the one to liquid products) and coke. The MTG process in TZFBR shows a clear improvement in stability, comparing it with its analogue in FBR, while keeping great similarity in yields to the different phases.